Kaempferol, a flavonoid, ameliorates hyperglycemia by attenuating the key enzymes of carbohydrate metabolism in streptozotocin–induced experimental diabetic rats - Govindasamy, Chandramohan (Progress in Nutrition, 2020)
Diabetes mellitus is a chronic metabolic disease with the highest rates of prevalence and mortality worldwide that is caused by an absolute or relative lack of insulin and/or reduced insulin activity, which results in hyperglycemia and abnormalities in carbohydrate, protein, and fat metabolism. The aim of this study was to investigate the effect of kaempferol on hepatic key enzymes of carbohydrate metabolism in streptozotocin-induced diabetic rats. An optimum dose of kaempferol (100 mg/kg body weight) was orally administered for 45 days to streptozotocin-diabetic rats for the assessment of glucose, insulin, hemoglobin (Hb), glycated hemoglobin (HbA1c), hepatic glycogen, and activities of carbohydrate metabolizing enzymes, such as glucokinase, glucose 6- phosphatase, fructose 1, 6-bisphosphatase and glucose-6-phosphate dehydrogenase in normal and streptozotocin-diabetic rats. Kaempferol at 100mg dose produced similar effects on all biochemical parameters studied as that of glibenclamide (600 mg/kg BW), a standard drug. These results showed that kaempferol has potential antihyperglycemic activity in streptozotocin-induced diabetic rats.